The Place and Possibilities of Digital Measuring Instruments in Cross - Fields - Karshiyev Zokhidjon (Genius Journals, 2023)
In this article, the conversion of the entered measured value into a digital code in digital measuring instruments occurs automatically. Automatic conversion of the measured value into a digital code is a sign of identification of a digital measuring instrument. Based on this, the article presents some types of digital meters for the quantitative qualities of oil and oil products and you will receive a conclusion on the measurement results.
Keywords: octanometer; gas chromatography; density